(untitled) (Research, Society and Development, 2022)
Tuberculosis (TB), caused by the bacterium Mycobacterium tuberculosis, is one of the oldest infectious diseases of humanity, although capable of effective treatment, remains an important public health problem worldwide, due to the wide geographic dispersion, emergence of multidrug-resistant cases and co-infection with HIV. This study seeks to trace the epidemiological profile, through a retrospective and descriptive analysis of TB cases notified in the health region of Vale do São Patrício II, comprising 8 municipalities located in the north center of the state of Goiás, during the period 2001 to 2020. For this, epidemiological variables were obtained secondarily through consultations with the Information System for Notifiable Diseases (SINAN) and the Information System on Mortality (SIM). Socioeconomic variables obtained from the National Household Sample Survey (PNAD) were also evaluated. In the period analyzed, 303 cases of patients with TB were notified in the São Patrício II health region, with an average annual incidence rate of 6.81/100,000 inhabitants. Being brown (57.10%), male (63.70%), and aged from 25 to 44 years (40.26%), representing most of the number, patients with incomplete elementary education and affected by the clinical pulmonary form (92.74%), with laboratory confirmation (61.06%). The distribution of TB incidence was positively associated with socioeconomic factors. Even with available vaccination, TB is an important public health problem, and it is imperative that more in-depth investigations into this pathology and investment in public policies to increase the percentage of cure, considering the difficulties of resources in the most affected locations and investments in continuing education for professionals and the population in general, in order to reduce the number of cases related to this pathology.